Antioxidant Activity Test Of Total Flavonoids Mistletoe Leaves (Dendrophthoe pentandra (L.) Miq) From False Ashoke Tree - Fahmi, Aliyah; NST, Rumondang Bulan; N, Hamonangan (Fakultas Farmasi, Universitas Gadjah Mada, 2016)
Research on the antioxidant activity test of total flavonoids mistletoe leaves (Dendrophthoe pentandra (L.) Miq) from false ashoke tree (Polyalthia longifolia) had been done. This study aimed to determine antioxidant activity of total flavonoids mistletoe leaves based on reduction method of free radicals 2.2- diphenyl-1-picrylhydrazyl (DPPH) 200 ppm using a UV Visible Spectrophotometer at maximum wavelength 516 nm was obtained Inhibition Concentration (IC50) amount 6,16 mg / L with the reduction percentage of 98.61% at 100 ppm which means it had a very strong antioxidant activity. Keywords: mistletoe leaves, Dendrophthoe pentandra (L.) Miq, antioxidant activity ,false ashoke tree